Multiple Focal Nodular Hyperplasia and Steatohepatitis: Atypical Imaging Characteristics - Robert P Myers; Dónal Downey; Subrata Chakrabarti; Paul J Marotta (Canadian Journal of Gastroenterology)
Focal nodular hyperplasia is a rare, benign condition of the liver. A 28-year-old woman with malignant melanoma, mild liver enzyme abnormalities, steatohepatitis and newly documented hepatic lesions is described. Ultrasound, computed tomography and magnetic resonance imaging suggested only areas of focal fatty sparing but could not eliminate the concern for metastases. A 99mtechnetium-labelled sulphur colloid scan, however, revealed areas of increased uptake consistent with multiple focal nodular hyperplasia. This diagnosis was ultimately confirmed with a liver biopsy. The investigation of a patient with a malignancy and expanding hepatic lesions is challenging. This case illustrates the usefulness of the 99mtechnetium-labelled sulphur colloid scan in the evaluation of patients with hepatic lesions.